Cover Me: Managers' Responses to Changes in Analyst Coverage in the Post-Regulation FD Period - Anantharaman, Divya; Zhang, Yuan (The Accounting Review, 2011)
ABSTRACT We show that managers increase the volume of public financial guidance in response to decreases in analyst coverage of their firms, particularly to decreases that are driven by exogenous reduction in brokerage firm size. Managers do not respond to increases in analyst coverage. The managerial guidance response to decreases in coverage reflects the trade-off between the marginal benefits from analyst coverage and the marginal costs of providing guidance. Specifically, the response is concentrated within firms engaging in equity issuance activities, firms with low stock liquidity, and firms with low current guidance levels. The response is also concentrated within firms whose remaining analyst pool is smaller in number and/or has a lower percentage of analysts who are positive about the firm or who belong to a large brokerage house. Overall, our results shed insights on the interaction between managers and analysts and on how the value of analysts, as perceived by managers, varies in the cross-section with underlying firm and analyst characteristics. Data Availability: All data used in this study are publicly available from sources identified in the text.